Effect of a Proprietary Commiphora mukul Gum Resin Extract and Medium-Chain Triglyceride Preparation (GU-MCT810) on hypoxia-inducible factor-1 pathway in HepG2 cell line - Cheppail Ramachandran,; Gilda M. Portalatin,; Karl-W Quirin,; Enrique Escalon,; Steven J. Melnick, (International Journal of Phytomedicine, 2015)
The heterodimeric transcription factor HIF-1 is responsible for the regulation of genes that facilitate adaptation and survival of cells under hypoxic conditions. HIF-1 gene expression is also associated with angiogenesis, glucose transport, nitric oxide synthase activity and cell proliferation through the regulation of hundreds of genes associated with HIF-1 pathway. GU-MCT810 is a nutraceutical ingredient complex that includes a Commiphora mukul (guggul) extract prepared by a supercritical CO2-co-solvent extraction with ethanol and medium chain triglyceride (MCT) oil composed of C8 and C10 fatty acids. Since cancer cells use glycolytic pathway, 2-deoxyglucose (2-DG) has been reported to inhibit the glycolysis. We have investigated the anticancer potential of GU-MCT810 with and without 2-DG in HepG2 human hepatoma cell line. Even though GU-MCT810 and 2-DG are individually weakly cytotoxic, the combination is synergistic with combination index (CI) values of 0.21, 0.22 and 0.88 at IC50, IC75 and IC90 levels, respectively. The combination also showed a synergistic inhibitory effect on ATP-synthesis in HepG2 cells. GU-MCT810 inhibits CoCl2-induced HIF-1α expression significantly in a dose-dependent manner with complete inhibition at 50 µg/ml concentration. GU-MCT810 upregulates Bax and p21 genes and down regulates Bcl-2, BNIP3 and mutant p53 genes associated with apoptosis. It also down regulates proteins associated angiogenesis (VEGF, VEGF-R), cell proliferation (IGF-2), glucose transport (GLUT1) and adaptogenesis (HSP70 and HSP90). These results indicate that GU-MCT810 can be combined with 2-DG for inhibition of HIF-1 pathway genes which would be useful for elimination of refractory cancer cells present in the hypoxic region of human tumors.